2017
DOI: 10.1002/jbmr.3112
|View full text |Cite
|
Sign up to set email alerts
|

N‐cadherin Regulation of Bone Growth and Homeostasis Is Osteolineage Stage–Specific

Abstract: N-cadherin inhibits osteogenic cell differentiation and canonical Wnt/β-catenin signaling in vitro. However, in vivo both conditional Cdh2 ablation and overexpression in osteoblasts lead to low bone mass. We tested the hypothesis that N-cadherin has different effects on osteolineage cells depending upon their differentiation stage. Embryonic conditional osteolineage Cdh2 deletion in mice results in defective growth, low bone mass and reduced osteoprogenitor number. These abnormalities are prevented by delaying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 48 publications
1
26
0
Order By: Relevance
“…To determine whether osteolineage cells may be present in the TME, we crossed the established tetracycline-dependent Tg(Sp7-tTA,tetO-EGFP/cre)1Amc/J (Osx-cre) to the B6.Cg-Gt(ROSA)26Sortm9(CAG-tdTomato)Hze/J (TdT) to generate the Osx-cre;TdT reporter mouse model ( Rodda and McMahon, 2006 ). When constitutively activated, TdT marks the entire osteolineage, including bone surface osteoblasts, osteocytes and bone marrow cells with mesenchymal stem and osteoprogenitor cell features; while delaying Osx-cre expression until postnatally restricts TdT targeting to committed osteoblasts and osteocytes ( Mizoguchi et al, 2014 ; Fontana et al, 2017 ). Therefore, Osx-cre;TdT mice and control animals carrying only the TdT transgene (WT;TdT) were kept on standard chow to allow constitutive embryonic transgene activation, or fed a doxycycline (doxy)-containing diet until weaning to suppress transgene activation until one month of age ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether osteolineage cells may be present in the TME, we crossed the established tetracycline-dependent Tg(Sp7-tTA,tetO-EGFP/cre)1Amc/J (Osx-cre) to the B6.Cg-Gt(ROSA)26Sortm9(CAG-tdTomato)Hze/J (TdT) to generate the Osx-cre;TdT reporter mouse model ( Rodda and McMahon, 2006 ). When constitutively activated, TdT marks the entire osteolineage, including bone surface osteoblasts, osteocytes and bone marrow cells with mesenchymal stem and osteoprogenitor cell features; while delaying Osx-cre expression until postnatally restricts TdT targeting to committed osteoblasts and osteocytes ( Mizoguchi et al, 2014 ; Fontana et al, 2017 ). Therefore, Osx-cre;TdT mice and control animals carrying only the TdT transgene (WT;TdT) were kept on standard chow to allow constitutive embryonic transgene activation, or fed a doxycycline (doxy)-containing diet until weaning to suppress transgene activation until one month of age ( Figure 1A ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, Osx-cre;TdT mice and control animals carrying only the TdT transgene (WT;TdT) were kept on standard chow to allow constitutive embryonic transgene activation, or fed a doxycycline (doxy)-containing diet until weaning to suppress transgene activation until one month of age ( Figure 1A ). We previously reported that doxy-fed mice display less than 1% of spontaneous recombination in the bone residing osteoblasts at weaning, but full transgene activation 1 month thereafter ( Fontana et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In development, N-cadherin plays an important role in morphogenetic processes during the formation of cardiac and neural tissues, and is involved in osteogenesis, skeletal myogenesis and maturation of the vasculature [ 28 – 32 ]. In adulthood, N-cadherin is expressed by numerous cell types including neural cells, endothelial cells, stromal cells and osteoblasts, and is integral to synapse function, vascular stability and bone homeostasis [ 30 , 33 – 36 ]. While N-cadherin is typically absent or expressed at low levels in normal epithelial cells, the aberrant expression of N-cadherin in epithelial cancer cells is a well-documented feature of epithelial malignancies, such as breast, prostate, urothelial and pancreatic cancer, and is associated with disease progression [ 37 – 40 ].…”
Section: The Functional Role Of N-cadherin In Solid Tumour Metastasismentioning
confidence: 99%
“…A recent in vivo study described a dual action of this protein on osteolineage cells depending upon their differentiation level. The authors demonstrated that N-cadherin maintains the pool of osteoprogenitor and stem cells and prevents the osteoblast differentiation of lineage-committed cells and function of mature osteoblasts 53 . In our research, we detected an increase of N-cadherin expression in MSCs cocultured with DRG neurons for 4 days, followed by a decrease three days later.…”
Section: Discussionmentioning
confidence: 99%